HISTORY, AUTHORITY, AND POWER: A Case of Religious Violence in Aceh (State Islamic University (UIN) of Sunan Ampel Surabaya, 2014)
This article discusses the way Islam transformed into an ideology that potentially used as justification for violence. By analising the case of the murder of Teungku Ayub, leader of a small circle for basic religious learning (pengajian) in Bireun, Aceh, in 2012, the study reveals to the role of Islam as an ideology of mass movement to cleanse deviant tenet (aliran sesat) among the Acehnese. This is because of two reasons. First, the term of the veranda of Mecca (serambi Mekkah) remains considered as “holy word” in the Acehnese society today, which supports any Islamic agenda of purifying Aceh from aliran sesat. Secondly, the adoption of Islam into a formal body of state (Aceh province) represented by the implementation of Islamic law (sharīʻah). Both reasons above strengthen ulama in Aceh to facilitate the mass movement in the name of religion as well as the rationale background of the murder of Teungku Ayub.